Development of number line estsimation in Chinese preschoolers: a comparison between numerical and non-numerical symbols - Li, Mengxia; Yang, Jiahui; Lei, Xiaohan (Frontiers in Psychology, 2024)
To examine the level of number line estimation (NLE) in Chinese children with respect to representations of both numerical (Arabic numerals) and non-numerical symbols (dots), a total of 192 Chinese preschoolers aged 4 and 5 participated in four different NLE tasks. These tasks were paired to evaluate the accuracy and patterns of children's estimations in both numerical and nonnumerical symbol contexts.Our findings indicate that, for Chinese preschoolers, relatively precise numerical symbol representations begin to emerge as early as 4 years of age. The accuracy of number line estimates for both 4-and 5-year-old children gradually increases in tasks involving both numerical and nonnumerical symbols. Additionally, the development and patterns observed in the number line estimates of 4-and 5-year-old Chinese preschoolers are similar in both numerical symbol and nonnumerical symbol tasks. These results indicate that the initiation of relatively precise numerical symbol representation and the turning point in the developmental trajectory, where the relatively precise representation for numerical symbols surpasses that of non-numerical ones, occur earlier in Chinese children than in their Western counterparts.